Effect of Flushing with Energy and Protein Source Diets on the Reproductive Performances of Meat Goats with High and Low Body Condition Scores (Global Journal of Science Frontier Research, 2016)
The objective of this experiment was to evaluate the effect of short-term flushing with energy and protein sources on the reproductive performances of meat goats for 21 days. A total of 180 Spanish and their crosses with Boer goats (Spanish X Boer) were randomly assigned to 6 treatments consisting of 2 body condition score (BCS) classes (Low and High) and 3 flushing treatments consisting of no supplementation (control), supplementation with protein mixture (PM) and combination of protein and energy (PE) in a 2 x 3 factorial arrangements. The results indicated that the BCS class had significant effect on pregnancy (P < 0.01) and kidding rates (P < 0.05) in which does in high body condition class had higher pregnancy and kidding rates than those in the low condition. The number of does diagnosed as pregnant was 67 and 81 and as non-pregnant was 23 and 9 for Low and High BCS does, respectively. Likewise, there were 24 and 11 does that did not kid and 66 and 79 that did for Low and High BCS, respectively. Litter size and weight was greater (P < 0.05) for Spanish X Boer than for Spanish does.
Keywords: body condition score; body weight; boer goats; flushing; reproductive traits; spanish goats